Dementia and hearing loss: A narrative review. (October 2019) - Ray, Manisha; Dening, Tom; Crosbie, Brian
Highlights: Hearing loss and dementia often occur together and hearing loss may be an independent risk factor for subsequent dementia. Several mechanisms may contribute to the association, including brain pathology but also social factors. Hearing loss is linked to multiple physical and psychological comorbidities in persons with dementia. Multiple barriers exist in both screening and treatment of hearing loss among people with dementia. Extended clinical trials are needed to establish whether treating hearing loss is effective in the prevention of dementia. Abstract: Dementia and hearing loss are both common among older people. The co-occurrence of the two conditions increases complexities in all aspects of an individual's care and management plan. There has been increasing research interest in the relationship between dementia and hearing loss in recent years. In this review we discuss the relationship between hearing loss and dementia, including hearing loss as a risk factor for dementia; the effects of dementia with hearing loss on affected persons' quality of life and the care they receive; screening and available interventions; and opportunities for prevention. We also discuss dementia and hearing loss in the care home setting, as the majority of residents have either, or indeed both, dementia and/or hearing loss. Several mechanisms have been suggested for how hearing loss and dementia may be related but the evidence for how these may operate together is still unclear. Similarly, although it is to be hoped that the active identification and management of hearing problems may help to reduce the future development of cognitive impairment, evidence for this is still lacking.